Né de la terre et du feu, les métaux - Reymond, Jean-Pierre, 1958-; Prunier, James, 1959-; Ten Eycm, Ann M. (Paris : Gallimard, 1987)
Surveys the history of metals and their uses, both ancient and modern.
Geschiedenis van de techniek en industrie (rubricering Patrick Viaene)
Includes index.
Keywords: Metals -- Juvenile literature; Metals